Dominica : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Dominica's recovery from Tropical Storm Erika (August 2015) has been slower than anticipated, with output growth of 1 percent in 2016, dragged down by a storm-related decline in manufacturing. Moreover, capacity constraints and unfavorable weather slowed public investment more than anticipated. Despite ample liquidity, bank credit to the private sector remains weak, although this is in part relieved by growing lending by credit unions. Growth is projected to accelerate to above 3 percent in 2017-18 on the back of a pickup in public investment and several large-scale private projects with citizenship-by-investment and grant financing.